Pathogenicity and virulence of bacterial strains associated with summer mortality in marine mussels (Perna canaliculus). Issue 12 (30th November 2022) - Azizan, Awanis; Alfaro, Andrea C; Jaramillo, Diana; Venter, Leonie; Young, Tim; Frost, Emily; Lee, Kevin; Van Nguyen, Thao; Kitundu, Eileen; Archer, Stephen D J; Ericson, Jessica A; Foxwell, Jonathan; et al.
Abstract: The occurrence of pathogenic bacteria has emerged as a plausible key component of summer mortalities in mussels. In the current research, four bacterial isolates retrieved from moribund Greenshell࣪ mussels, Perna canaliculus, from a previous summer mortality event, were tentatively identified as Vibrio and Photobacterium species using morpho-biochemical characterization and MALDI-TOF MS and confirmed as V. celticus, P. swingsii, P. rosenbergii, and P. proteolyticum using whole genome sequencing. These isolates were utilized in a laboratory challenge where mussels were injected with cell concentrations ranging from 10 5 to 10 9 CFU/mussel. Of the investigated isolates, P. swingsii induced the highest mortality. Additionally, results from quantitative polymerase chain reaction analysis, focusing on known virulence genes were detected in all isolates grown under laboratory conditions. Photobacterium rosenbergii and P. swingsii showed the highest expression levels of these virulence determinants. These results indicate that Photobacterium spp. could be a significant pathogen of P. canaliculus, with possible importance during summer mortality events. By implementing screening methods to detect and monitor Photobacterium concentrations in farmed mussel populations, a better understanding of the host–pathogen relationship can be obtained, aiding the development of a resilient industry in a changing environment. Abstract : Bacterial strains were isolated from summer mortality events in moribund Greenshell࣪ mussels, and one of these, Photobacterium swingsii was found for the first time to cause the highest mortality in mussels ( P. canaliculus ) in a controlled experiment.